The Effect of Habits of Type 2 DM Patients on Blood Cholesterol Levels - setiawan, Muh Azdar Setiawan; Ira, Ira Indriasari Ruslan; Wenty, Darmayanita Wenty (Program Study of Medical Laboratory Technology , Politeknik Bina Husada Kendari, 2024)
ABSTRACT Teenagers tend to spend a lot of food at home and often choose fast food. This condition can lead to increased food intake, decreased activity, and increased blood sugar levels. As a result, levels interfere with glucose metabolism. This study aims to see the influence between the habits of type 2 DM patients on cholesterol levels. The research method used was an experiment using quantitative data retrospectively with an observational approach where the sample was selected incidentally and analysed using the SEM method with a total sample of 32 people. The results showed that the variable habits of type 2 DM patients had a P-value below 0.05 on the variable cholesterol levels with indicators of LDL levels and triglyceride levels. The conclusion of this study is that the habits of patients with type 2 diabetes have a significant influence on cholesterol levels. Keywords : Diabetes Mellitus, Cholesterol level, SEM